Steam trains - Garratt, Colin Dennis (New York : Gallery Books, 1984)
Shows trains still in use around the world, explains why the use of steam locomotives is declining, and describes the basic types of trains
Keywords: Locomotives -- History; Railroads -- History; Locomotives